Synergy Of Artificial Intelligence, Strategic Location, and Digital Marketing in Enhancing Logistics Efficiency and Consumer Satisfaction in E-Commerce - Bernadetta Anita Jeri S; Syahrudin Marpaung; Sulaiman Ahmad; Mardelia Desfrida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid growth of e-commerce has driven companies to seek more effective strategies to enhance logistics efficiency and customer satisfaction. This article examines the synergy between artificial intelligence, strategic location determination, and digital marketing in supporting the performance of digital supply chains. This multidimensional approach demonstrates that integrating cutting-edge technologies with precise location strategies and data-driven marketing can create superior customer experiences and more efficient operational costs. This study is based on a literature review of ten recent related studies. Moreover, it highlights consumer behavior shifts due to the digitalization and globalization of supply chains.